Identifying Sequence Determinants of Reduction Potentials of Metalloproteins - Perrin, Bradley Scott (2013)
The reduction potential of an electron transfer protein is one of its most important functional characteristics. While the type of redox site and the protein fold are the major determinants of the reduction potential of a redox active protein, its amino acid sequence may tune the reduction potential as well. Thus, homologous proteins can often be divided into different classes, with each class characterized by a biological function and a reduction potential. Site-specific mutagenesis of the sequence determinants of the differences in the reduction potential between classes should change the reduction potential of a protein in one class to that of the other class. Here, a procedure is presented that combines energetic and bioinformatics analysis of homologous proteins for identifying sequence determinants that are also good candidates for site-specific mutations, using the [4Fe-4S]-ferredoxins and the [4Fe-4S]-HiPIPs as examples. This procedure is designed to guide site-specific mutations or more computationally expensive studies, such as molecular dynamics simulations. To make the procedure more accessible to the general scientific community, it is being implemented into CHARMMing, a web-based portal, with a library of density functional theory results for the redox site that used in the set up of Poisson-Boltzmann continuum electrostatics calculations for the protein energetics.